In situ study on camouflage behavior of Abdopus aculeatus (Octopodidae) (D’Orbigny, 1834) on the marine water of Panjang island, Buton, Southeast Sulawesi - Jeni Jeni; Dwi Listyorini; Endang Suarsini (The East Java Biological Society, 2018)
Abdopus aculeatus has good camouflage capabilities in nature. The objective of this study is to obtain information on the camouflage behavior of Abdopus aculeatus in nature (in situ). We used an explorative description to observe the camouflage behavior of 24 octopus samples at a number of points on the Panjang Island, Buton Regency. Abdopus aculeatus was identified molecularly using a mtDNA COI blast to determine the target species of observation. Any of the camouflage behavior found was documented and analyzed descriptively. Generally, there are four forms of observations for camouflage behavior; matching body color to wide array of natural background, immersing itself in the sand, resembling a specific object, and being part of the objects surrounding. The various camouflages patterns obtained show a process of defense evolution in minimizing the detection of predators or octopus prey.